Improving throughput in a youth mental health service. Issue 3 (18th April 2017) - Coates, Dominiek; Howe, Deborah
Abstract : Purpose: The discrepancy between increasing demand and limited resources in public mental health is putting pressure on services to continuously review their practices and develop innovative models of care that redress this discrepancy. To ensure the service models continue to meet the needs of all stakeholders, children and young people's mental health (CYPMH) conducts regular reviews of its service models. Accordingly, the youth mental health (YMH) model at CYPMH has evolved significantly over time in response to the needs of young people and service demand. The purpose of this paper is to outline the findings of a recent review of the YMH service, and the subsequent changes to the service model. Design/methodology/approach: Informed by a participatory action philosophy, feedback was sought from staff on the service model through a range of methods including a questionnaire, staff consultations through a working party and interviews. This feedback was used to redesign the model, which was then evaluated again. Findings: Staff identified a number of challenges with the service model and a range of service improvement solutions. The key issues included exceedingly high caseloads, workplace tensions, and fragmentation of the client journey. This paper outlines the primary solution to these key concerns, namely, the introduction of brief intervention (BI) as the entry point to the service. Originality/value: BI approaches provide a solution to overly high caseloads as the direct and focussed approach of BI generally reduces the number of sessions people need. BI is an important addition to other treatment options and should be seen as a valid component of the continuum of mental healthcare.